New Onset Intraparenchymal Hemorrhage Following Infant Feeding Tube-Guided Evacuation of Chronic Subdural Hematoma: A Report of Two Cases - Khandelwal, Ankur; Singh, Gyaninder P.; Garg, Mayank; Chaturvedi, Arvind (Journal of Neuroanaesthesiology and Critical Care, 2019)
Chronic subdural hematoma (CSDH) is one of the most common neurosurgical conditions and is usually treated by simple burr-hole drainage. Prognosis is usually good unless complications occur. Use of infant feeding tube (IFT) for irrigation of hematoma in case of CSDH with septum is a common practice. However, it poses a significant risk. We present two cases of intraparenchymal hemorrhage as a complication of CSDH evacuation in which IFT was used for irrigation.
Keywords: chronic subdural hematoma; infant feeding tube; intraparenchymal hemorrhage